Criterios técnicos de evaluación de fuentes no convencionales de energía en un distrito térmico en Colombia (2024)
"This monograph explores the integration of thermal districts in Colombian cities as a key strategy to promote sustainability, energy efficiency, and the reduction of environmental impact. Supported by Resolution 41286 of 2016 and the Indicative Action Plan 2017-2022, these systems stand out for their ability to enhance energy efficiency and replace technologies with a high environmental impact, in alignment with national policies for the mitigation of greenhouse gases (GHGs). These issues demand innovative solutions that ensure green urban growth and sustainable social and economic well-being. In this context, the integration of unconventional energy sources emerges as an essential solution to mitigate the negative impacts associated with traditional energy production and consumption methods. The technical evaluation of unconventional energy sources is crucial to ensure the viability and effectiveness of thermal districts in Colombia. A comprehensive analysis that addresses technical, economic, and environmental aspects is fundamental to facilitate a transition towards a cleaner and more efficient energy system. This monograph identifies key criteria for the successful implementation of unconventional technologies, providing a practical guide that supports sustainable urban development and significantly contributes to reducing environmental impacts in Colombian cities. The incorporation of unconventional energy sources, such as solar, wind, geothermal, and biomass, is vital to achieve these objectives. Each source presents unique characteristics and benefits that, when adequately evaluated, can offer effective solutions to the energy challenges faced by Colombian cities. A rigorous technical assessment of these sources, considering conversion efficiency, generation capacity, and resource availability, is essential to select the most suitable options and ensure their successful integration into thermal districts. In conclusion, detailed analysis and proper implementation of unconventional sources can facilitate a transition towards a greener and more efficient energy system, supporting sustainable urban development and significantly contributing to the mitigation of environmental impacts."